Gród Krzywoustego? Poszukiwanie mitu fundacyjnego i piastowska legitymizacja na przykładzie organizacji obchodów 840-lecia Jeleniej Góry w 1948 r. - Szajda, Marek (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2023)
The commemoration of 840 years of Jelenia Góra, organized in 1948, werea propagand a event based on narratives created at that time, concerning the history oft hose territories, in particular – the legacy of Piast dynasty. Such narration about the past was possible not only because of the communist vision of the past forced top-down on the society, but also thanks to stories about the origins of the medieval settlement whiche merged at grass-roots level.
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne